2014
DOI: 10.1159/000362366
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transmitted HIV-1 Drug Resistance Remains Low in Guangxi, China, Eight Years after Scale-Up of Highly-Active Antiretroviral Therapy

Abstract: Objectives: Highly-active antiretroviral therapy (HAART) was scaled up in Guangxi, China in 2005. The number of individuals receiving free HAART increased dramatically from June 2010 under the Guangxi Government's anti-HIV programme. We aimed to determine the prevalence of HIV-transmitted drug resistance (TDR) of Guangxi. Methods: HIV-positive, antiretroviral-naive individuals were recruited from the east (Hezhou), south (Qinzhou), west (Baise), north (Guilin) and centre (Laibin) of Guangxi. The pol gene of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
4
18
2
Order By: Relevance
“…In the current study, no drug resistance mutations were assessed in the NNRTI class among naïve patients; there is a concordance between this result and 2 previous studies [10,22]. However, the result is inconsistent with other studies reporting NNRTI mutations in naïve patients [1,23]. It seems that further research is needed to uncover the most likely reason for this incompatibility.…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, no drug resistance mutations were assessed in the NNRTI class among naïve patients; there is a concordance between this result and 2 previous studies [10,22]. However, the result is inconsistent with other studies reporting NNRTI mutations in naïve patients [1,23]. It seems that further research is needed to uncover the most likely reason for this incompatibility.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, the overall TDR prevalence among newly diagnosed ART-naïve individuals in Lingshan County was 5.5%, reaching a moderate level according to the WHO SDRM list, which is slightly higher than those previously estimated in the whole of Guangxi (4.6% in 2009 and 3.3% in 2012–2013) [40, 42]. It has been reported that transmission clusters contribute to the spread of TDR in relatively closed populations [43, 44].…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, three genotypes, including CRF08_BC, CRF01_AE, and CRF07_BC, were identified among ART-naïve patients. Among them, CRF08_BC was the dominant subtype (70.6%) followed by CRF01_AE (24.4%), which is also quite different from the genotype distribution in China and Guangxi, where CRF01_AE has been the dominant subtype for several years [38-40]. However, the predominance of CRF08_BC in IDUs was also found in other places with a high prevalence of drug use in China, for example Zhaotong City in Yunnan [41] and Baise City in Guangxi [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subtype distribution in Guangxi is approximately 75% CRF01AE and 25% B or BC recombinants. [8][9][10] Previous research in Thailand estimated that the FRR was 0% using a cutoff of 1.0 OD-n for 128 samples from CRF01_AE-infected subjects. 4 Additionally, individuals infected with subtype B and C historically have a low FRR.…”
mentioning
confidence: 99%